Current Status of Knowledge about and Attitudes Toward the Hepatitis B Virus at A Private University in Southern Vietnam: A Cross-sectional Self-reported Study - Quang Vo, Dr. Trung (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Hepatitis B is a common infectious disease and can be life-threatening. The rate of hepatitis B virus (HBV) infection is increasing, especially in developing countries, including Vietnam. Aims: The aim of this study is to explore knowledge about and attitudes toward HBV among undergraduate students at a private university in southern Vietnam. Subjects and Methods: A cross-sectional self-reported study was carried out among 535 undergraduate pharmacy students between December 2017 and February 2018 at the Faculty of Pharmacy, Lac Hong University. All data analysis was performed using SPSS 20.0. Results: Out of 620 distributed questionnaires, 535 were returned - a response rate of 86.3%. Out of a total of 535 students surveyed, 174 (32.5%) were male and 361 (67.5%) were female pharmacy students. Overall, there was not a significant variance in knowledge between males and females regarding the knowledge about hepatitis B. However, the attitude score of females was higher than that of males, with a mean score of 3.37 Â± 0.09 for males and 3.42 Â± 0.14 for females. There was no difference in knowledge between males and females, but there was a difference in attitudes toward hepatitis B vaccination. Conclusions: The overall knowledge of pharmacy students showed satisfactory outcomes. However, it is necessary to improve attitudes about HBV vaccine by disseminating information to students and the public, especially by showing friends and family the relevant HBV information and conducting a health education campaign for people to help them adopt proper attitudes toward a self-care educational program.